Productivity of Micronutrients from Integrated Aquaculture Agriculture Systems: Evidence from Bangladesh - Ignowski, Liz; Belton, Ben (WorldFish, 2022)
Abstract accepted for presentation at the Annual Meeting of the World Aquaculture Society held in Singapore on 29 November to 2 December 2022. The presentation discussed the survey results on measuring micronutrient productivity in integrated aquatic farming systems for nutrition sensitive agriculture in Bangladesh.